1992
DOI: 10.1159/000177720
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient Status in Females during a 24-Week Fitness-Type Exercise Program

Abstract: Thiamin, riboflavin, vitamin B6, magnesium, iron and zinc status, assessed from blood samples, was studied during a 24-week fitness-type exercise program. Subjects in exercise (n = 21) and control (n = 18) groups were female university students, aged 18-33 years. Erythrocyte (E) transketolase and glutathione activation coefficient, serum magnesium, zinc and ferritin, blood hemoglobin concentration and mean corpuscular volume were similar in both groups throughout the entire study. E-aspartate aminot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 17 publications
0
31
0
1
Order By: Relevance
“…A 24 week fitness-type exercise program did not appreciably affect vitamin B6 status (EAST-AC) in young women (61), nor did a study on exercise-induced lactate in young adults (62), or moderate exercise among women (134). A transient increase in plasma PLP that decreased after 1 hr was observed among three groups of women (young, young/untrained, post-menopausal/untrained) during the exercise period (134).…”
Section: Demographics and Lifestylementioning
confidence: 99%
“…A 24 week fitness-type exercise program did not appreciably affect vitamin B6 status (EAST-AC) in young women (61), nor did a study on exercise-induced lactate in young adults (62), or moderate exercise among women (134). A transient increase in plasma PLP that decreased after 1 hr was observed among three groups of women (young, young/untrained, post-menopausal/untrained) during the exercise period (134).…”
Section: Demographics and Lifestylementioning
confidence: 99%
“…Similar results are expected in female athletes and active women. For instance, Fogelholm (1992) assessed thiamin status before and after a 24-week exercise program in female college students (18 to 33 years). No changes were seen in biochemical markers of thiamin after the 24-week exercise program.…”
Section: Dietary Intake and Status Of Thiamin In Active Adultsmentioning
confidence: 99%
“…Some studies reported thiamin status to be adequate8 9 and, moreover, that exercise training does not appear to alter thiamin status 10. Similarly, studies on cobalamin also observed adequate status in athletes 4.…”
Section: Vitamin Bmentioning
confidence: 99%
“…Data on riboflavin are mixed, with some studies reporting poor status in athletes12 13 and it has been suggested that riboflavin requirements may be higher than the recommended nutritional intake (RNI) for athletes than for the general population 4. Similarly, poor pyridoxine status in male and female athletes has been documented in some studies 10 12. Exercise training has been found to increase pyridoxine requirements due to greater losses and turnover suggesting that athletes undergoing heavy training might require more pyridoxine than current RNI 14.…”
Section: Vitamin Bmentioning
confidence: 99%